A hope for ineffective antibiotics to return to treatment: investigating the anti-biofilm potential of melittin alone and in combination with penicillin and oxacillin against multidrug resistant-MRSA and -VRSA - Jalalifar, Saba; Razavi, Shabnam; Mirzaei, Rasoul; Irajian, Gholamreza; Pooshang Bagheri, Kamran (Frontiers in Microbiology, 2024)
Background The emergence and rapid spread of multi-drug resistant (MDR) bacterial strains, such as methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant S. aureus (VRSA), have posed a significant challenge to the medical community due to their ability to form biofilm and develop resistance to common antibiotics. Traditional antibiotics that were once effective in treating bacterial infections are now becoming increasingly ineffective, leading to severe consequences for patient outcomes. This concerning situation has called for urgent research to explore alternative treatment strategies. Recent studies have shown that antimicrobial peptides (AMPs) hold promise as effective agents against biofilm-associated drug-resistant infections as well as to enhance the efficacy of conventional antibiotics. Accordingly, we aimed to investigate the antimicrobial and antibiofilm effects of melittin AMP, both alone and in combination with penicillin and oxacillin, against biofilm-forming MDR-MRSA and -VRSA. Methods In this study, we investigated the kinetics of biofilm formation and assessed various parameters related to the antimicrobial and antibiofilm efficacy of melittin and antibiotics, both alone and in combination, against MDR-MRSA and -VRSA. The antimicrobial parameters included the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), Fractional Inhibitory Concentration Index (FICi), Fractional Bactericidal Concentration Index (FBCi), and the antibiofilm activity of melittin and antibiotics indicated by the Minimum Biofilm Inhibitory Concentration (MBIC), Minimal Biofilm Eradication Concentration (MBEC), Fractional Biofilm Inhibitory Concentration Index (FBICi), and Fractional Biofilm Eradication Concentration Index (FBECi). Results The MIC results showed that all S. aureus isolates were resistant to penicillin (≥0.25 μg/mL), and 66% of isolates were resistant to oxacillin. The geometric means of the MIC values for penicillin, oxacillin, and melittin were 19.02, 16, and 1.62 μg/ml, respectively, and the geometric means of the MBC values for penicillin, oxacillin, and melittin were 107.63, 49.35, and 5.45 μg/ml, respectively. The study revealed that the combination indexes of melittin-penicillin and melittin-oxacillin, as determined by FIC values against all isolates, were 0.37 and 0.03, respectively. Additionally, melittin-penicillin and melittin-oxacillin exhibited combination indexes based on FBC values against all isolates at 1.145 and 0.711, respectively. Besides, melittin inhibited the biofilm formation of all S. aureus isolates, with MBIC values ranging from 10 to 1.25 μg/mL, and MBEC values ranging from 40 to 10 μg/mL. Generally, the combination indexes of melittin-penicillin and melittin-oxacillin, determined using FBIC values against all isolates, were 0.23 and 0.177, respectively. Moreover, melittin-penicillin and melittin-oxacillin typically had combination indexes based on FBEC values against all isolates at 5 and 2.97, respectively. Conclusion In conclusion, our study provides evidence that melittin is effective against both planktonik and biofilm forms of MRSA and VRSA and exhibits significant synergistic effects when combined with antibiotics. These results suggest that melittin and antibiotics could be a potential candidate for further investigation for in vivo infections caused by MDR S. aureus. Furthermore, melittin has the potential to restore the efficacy of penicillin and oxacillin antibiotics in the treatment of MDR infections. Applying AMPs, like melittin, to revive beta-lactam antibiotics against MRSA and VRSA is an innovative approach against antibiotic-resistant bacteria. Further research is needed to optimize dosage and understand melittin mechanism and interactions with beta-lactam antibiotics for successful clinical applications.